RADIO PROPER MOTIONS OF WOLF-RAYET STARS - S. Dzib (Revista Mexicana de Astronomía y Astrofísica, 2009)
We present the analysis of observations taken from the Very Large Array archive of sixWolf-Rayet stars with radio emission, with the purpose of determining their proper motions. Typically, these observations cover periods of 10 to 20 years. To verify the method, we included WR 140 in the sample, and found that the proper motions determined by us are a few times more accurate than, and consistent within noise, with those of Hipparcos. The other ve WR stars were not studied by Hipparcos and we report their proper motions for the rst time. The proper motions for WR 145a = Cyg X-3 are consistent with the source being stationary with respect to its local standard of rest and suggest that the black hole in this binary system formed by direct collapse of a massive star, without expulsion of a supernova remnant.